The influence of CdCl2 layer and annealing process on the structural and electrical properties of CdTe films - Razooqi, Mohammed A. (Iraqi Journal of Physics, 2019)
A polycrystalline CdTefilms have been prepared by thermal evaporation technique on glass substrate at room temperature. The films thickness was about700±50 nm. Some of these films were annealed at 573 K for different duration times (60, 120 and 180 minutes), and other CdTe films followed by a layer of CdCl2 which has been deposited on them, and then the prepared CdTe films with CdCl2 layer have been annealed for the same conditions. The structures of CdTe films without and with CdCl2 layer have been investigated by X-ray diffraction. The as prepared and annealed films without and with CdCl2 layer were polycrystalline structure with preferred orientation at (111) plane. The better structural properties have been observed in presence of CdCl2 layer. The D.C conductivity for CdTe films with CdCl2 layershowed higher values. The electrical activation energy influenced with increasing duration times of annealing. Hall Effect measurement was indicated that all CdTe films are p-type. The carrier concentration, Hall mobility and the carrier life time wereaffected by increasing duration times of annealing.